Psychopharmacology of depression - Leonard, Brian (Henry Stewart Talks, 2007)
Noradrenergic pathways in depression, Serotonergic pathways in normal brain and in depression, Desirable features of an antidepressant, Drugs used in the treatment of depression, Classification of antidepressants, Tricyclic antidepressants and monoamine, Oxidase inhibitors: sites of action, The relationship between pre- and post-synaptic structures, Electroconvulsive shock therapy